2018
DOI: 10.1002/ana.25327
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Protocadherin‐12Leads to Diencephalic‐Mesencephalic Junction Dysplasia Syndrome

Abstract: DMJD patients have biallelic mutations in PCDH12 and lack of protein expression. These patients present with characteristic microcephaly and abnormalities of white matter tracts. Such pathogenic variants predict a poor outcome as a result of brainstem malformation and evidence of white matter tract defects, and should be added to the phenotypic spectrum associated with PCDH12-related conditions. Ann Neurol 2018;84:646-655.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…All members of the δ1-Pcdh family and the majority of the δ2-Pcdh family, with the exception of Pcdh18, have been associated to the regulation of dendritic initiation, growth, morphology, arbor refinement, and spine formation ( Yasuda et al, 2007 ; Piper et al, 2008 ; Bruining et al, 2015 ; Wu et al, 2015 ; Schoch et al, 2017 ; Bassani et al, 2018 ; Chang et al, 2018 ). To date, roles in axon growth, branching, guidance, and fasciculation have been described for Pcdh7 and for almost all of the δ2-Pcdhs except Pcdh8 ( Aoki et al, 2003 ; Uemura et al, 2007 ; Nakao et al, 2008 ; Piper et al, 2008 ; Leung et al, 2013 , 2015 ; Biswas et al, 2014 ; Hayashi et al, 2014 ; Cooper et al, 2015 ; Asakawa and Kawakami, 2018 ; Guemez-Gamboa et al, 2018 ). While specific synaptic roles have not yet been directly demonstrated for δ1-Pcdhs, they have been suggested to participate in synaptic maintenance and plasticity based on their expression at synapses and interaction with PP1α ( Yoshida et al, 1999 ; Vanhalst et al, 2005 ; Kim et al, 2007 ; Bruining et al, 2015 ).…”
Section: Expression and Roles Of Pcdhsmentioning
confidence: 99%
“…All members of the δ1-Pcdh family and the majority of the δ2-Pcdh family, with the exception of Pcdh18, have been associated to the regulation of dendritic initiation, growth, morphology, arbor refinement, and spine formation ( Yasuda et al, 2007 ; Piper et al, 2008 ; Bruining et al, 2015 ; Wu et al, 2015 ; Schoch et al, 2017 ; Bassani et al, 2018 ; Chang et al, 2018 ). To date, roles in axon growth, branching, guidance, and fasciculation have been described for Pcdh7 and for almost all of the δ2-Pcdhs except Pcdh8 ( Aoki et al, 2003 ; Uemura et al, 2007 ; Nakao et al, 2008 ; Piper et al, 2008 ; Leung et al, 2013 , 2015 ; Biswas et al, 2014 ; Hayashi et al, 2014 ; Cooper et al, 2015 ; Asakawa and Kawakami, 2018 ; Guemez-Gamboa et al, 2018 ). While specific synaptic roles have not yet been directly demonstrated for δ1-Pcdhs, they have been suggested to participate in synaptic maintenance and plasticity based on their expression at synapses and interaction with PP1α ( Yoshida et al, 1999 ; Vanhalst et al, 2005 ; Kim et al, 2007 ; Bruining et al, 2015 ).…”
Section: Expression and Roles Of Pcdhsmentioning
confidence: 99%
“…While many protocadherins are specifically expressed in the central nervous system (Kim et al, 2011), PCDH12 was initially identified in mouse endothelial cells (Telo' et al, 1998). In humans, PCDH12 is well expressed in placenta, lung, and spleen and at lower level in brain (GTEx, Hum-anProteinAtlas, biogps.org data) (Bouillot et al, 2011;Guemez-Gamboa et al, 2018). Functional analysis on induced pluripotent stem cells obtained from controls' and patients' fibroblasts showed the Mutations in PCDH12 have been implicated in an autosomal recessive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…exon of PCDH12 have been implicated in a neurodevelopmental disorder (OMIM: 251280) (Figure 1a) (Aran et al, 2016;Guemez-Gamboa et al, 2018;Suzuki-Muromoto et al, 2018;Vineeth et al, 2019). Consistent with nonsense-mediated decay, two of these mutations were associated with low expression of the mutated transcript (Aran et al, 2016;Vineeth et al, 2019).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Recently, biallelic loss of function variants in the protocadherin 12 gene ( PCDH12 ), encoding a cell surface protein promoting cell adhesion and neurite outgrowth, have been identified in 14 patients with DMJ dysplasia from eight independent families. Patients presented a peculiar clinical-radiological phenotype characterized by progressive microcephaly, severe cognitive impairment, dysmorphic facies, variable spasticity and epilepsy, DMJ dysplasia with midbrain ventral cleft, callosal hypoplasia, and in most cases also calcifications (Guemez-Gamboa et al , 2018). Of note, PCDH12 mutations were found in two of the three families originally described (Zaki et al , 2012), while no pathogenic variants were identified in the third family with a different phenotype of massively dilated lateral ventricles, further supporting the hypothesis of different genetic mechanisms underlying DMJ disorders.…”
Section: Discussionmentioning
confidence: 99%